Design, synthesis and biological evaluation of naringenin carbamate derivatives as potential multifunctional agents for the treatment of Alzheimer's disease. (1st October 2021) - Wu, Jiarui; Kou, Xiaodi; Ju, Hui; Zhang, Hongwei; Yang, Aihong; Shen, Rui
Graphical abstract: Abstract: A series of naringenin derivatives were designed and synthesized as multifunctional anti-Alzheimer's disease (AD) agents. The results showed that these derivatives displayed moderate-to-good acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) inhibitory activities at the micromolar range (IC50, 12.91 ~ 62.52 μM for AChE and 0.094 ~ 13.72 μM for BuChE). Specifically, compound 1 showed the highest inhibitory activity against BuChE with the IC50 value of (0.094 ± 0.0054) μM. A Lineweaver-Burk plot and molecular docking studies demonstrated that 1 targeted both the catalytically active site (CAS) and the peripheral anion site (PAS) of BuChE. Besides, all derivatives showed excellent hydroxyl free radicals (·OH) scavenging ability than vitamin C and cyclic voltammetry results displayed that 1 could effectively scavenge superoxide anion radical (·O2 – ). In addition, compound 1 displayed good metal chelating properties and had anti-Aβ aggregation activities. Therefore, compound 1 might be the potential anti-AD agent for further developments.